Knowledge and Willingness to Utilize Hepatitis B Preventive Measures among Pregnant Women in Ado-Ekiti, Southwest, Nigeria - Idowu Pius Ade-Ojo; Adefunke Olarinre Babatola; Temitope Olumuyiwa Ojo; Ezra Olatunde Ogundare; Tosin Agbesanwa; Adewuyi Temidayo Adeniyi; Omolola Alao; Oladele Simeon Olatunya; Joseph Olusesan Fadare (Interdisciplinary Perspectives on Infectious Diseases)
Introduction. Mother-to-child transmission remains an important mode of transmission of hepatitis B infection particularly in endemic areas. The knowledge and practices of pregnant women about mother-to-child transmission (MTCT) of hepatitis B virus (HBV) may influence the uptake of strategies to reduce mother-to-child transmission of infection. Objectives. This study assessed the knowledge and willingness to uptake hepatitis B virus infection preventive services among pregnant women in Ado-Ekiti, Nigeria. Methods. This was a cross-sectional study that involved 373 pregnant women at the Ekiti State University Teaching Hospital (EKSUTH) and Maternal Child Specialist Clinics, Ado-Ekiti, Nigeria. A structured questionnaire was used to assess their knowledge, practices, and perceptions about MTCT of hepatitis B infection. Results. Only 52.5% (196) of the respondents had good knowledge, although the majority 290 (77.7%) had heard of hepatitis B infection prior to the survey. Only 147 (39.4%) of the respondents had ever had hepatitis B screening. More persons with professional jobs had good knowledge about hepatitis B infection compared with other occupations (p<0.001). However, more respondents aged 30–34 years had poor knowledge about hepatitis B infection compared with other age groups (p=0.045). Respondents with good knowledge about hepatitis B infection were willing to uptake hepatitis B infection prevention services (p<0.001) Conclusion. This study showed that respondents with professional jobs had good knowledge about hepatitis B infection and those who had good knowledge about the infection were willing to utilize hepatitis B preventive measures. Awareness of MTCT of HBV did not translate into good practice as only few respondents had screened for hepatitis B. There is a need to intensify education about modes of transmission of hepatitis B infection with an emphasis on promoting good preventive practices.